Wild interdisciplinarity: ethnography and computer science - Goulden, Murray; Greiffenhagen, Christian; Crowcroft, Jon; McAuley, Derek; Mortier, Richard; Radenkovic, Milena; Sathiaseelan, Arjuna (Taylor & Francis, 2016)
Drawing on the experiences of a novel collaborative project between sociologists and computer scientists, this paper identifies a set of challenges for fieldwork that are generated by this wild interdisciplinarity. Public Access Wi-Fi Service was a project funded by an ‘in-the-wild’ research programme, involving the study of digital technologies within a marginalised community, with the goal of addressing digital exclusion. We argue that similar forms of research, in which social scientists are involved in the deployment of experimental technologies within real world settings, are becoming increasingly prevalent. The fieldwork for the project was highly problematic, with the result that few users of the system were successfully enrolled. We analyse why this was the case, identifying three sets of issues which emerge in the juxtaposition of interdisciplinary collaboration and wild setting. We conclude with a set of recommendations for projects involving technologists and social scientists.